2016
DOI: 10.1007/s00330-016-4442-z
|View full text |Cite
|
Sign up to set email alerts
|

Decreased stage migration rate of early gastric cancer with a new reconstruction algorithm using dual-energy CT images: a preliminary study

Abstract: ObjectivesTo evaluate the potential value of advanced monoenergetic images (AMEIs) on early gastric cancer (EGC) using dual-energy CT (DECT).Methods31 EGC patients (19 men, 12 women; age range, 38–81 years; mean age, 57.19 years) were retrospectively enrolled in this study. Conventionally reconstructed polyenergetic images (PEIs) at 120 kV and virtual monoenergetic images (MEIs) and AMEIs at six different kiloelectron volt (keV) levels (from 40 to 90 keV) were evaluated from the 100 and Sn 140 kV dual energy i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 29 publications
0
6
0
Order By: Relevance
“…Tilman Hickethiera et al also verified MEI (+) 40 keV venous-phase chest CT examinations can reduce doses and improve the quality of images [ 10 ]. The MEI (+) technique performs recombination based on spatial frequency, which reduces the image noise at lower levels and improves the image contrast at higher energies to obtain the best image contrast [ 20 ]; thus, MEI (+) improves the potential of evaluation for T staging [ 21 ]. Combined with the high contrast of MEI (+) 40 keV and obvious enhancement of the lesion in the venous phase, the depth of lesion involvement to the esophageal wall was subjectively evaluated.…”
Section: Discussionmentioning
confidence: 99%
“…Tilman Hickethiera et al also verified MEI (+) 40 keV venous-phase chest CT examinations can reduce doses and improve the quality of images [ 10 ]. The MEI (+) technique performs recombination based on spatial frequency, which reduces the image noise at lower levels and improves the image contrast at higher energies to obtain the best image contrast [ 20 ]; thus, MEI (+) improves the potential of evaluation for T staging [ 21 ]. Combined with the high contrast of MEI (+) 40 keV and obvious enhancement of the lesion in the venous phase, the depth of lesion involvement to the esophageal wall was subjectively evaluated.…”
Section: Discussionmentioning
confidence: 99%
“…In all studies, the optimal energy levels for VMI+ reconstructions recommended by researchers for different tumors were typically in the range of 50-60 keV. The optimal energy levels of reconstruction recommended for various cancers/tumors are as follows: 50 keV for cutaneous malignant melanomas and renal cell carcinomas (RCCs) in the corticomedullary-phase of enhancement (19,20); 55 keV for head and neck cancers, lung cancers, and hypervascular liver tumors (21-23); 60 keV for RCCs in the nephrogenic-phase of enhancement, gastrointestinal stromal tumors, and abdominal metastases, and hypo-attenuating liver metastases from colorectal cancers (19,24,25); low energy levels especially 40 and 50 keV for pancreatic adenocarcinomas (26); and 40 keV (a small number of studies) for malignant tumors in the head and neck region, metastatic spinal tumors, and early gastric cancer (27)(28)(29)(30). Concerning head and neck malignancies, Albrecht et al found that 55 keV reconstructions could yield the best subjective image quality (21); however, May et al recommended 40 keV for optimal image quality (28).…”
Section: Tumormentioning
confidence: 99%
“…Martin et al (19) analyzed the reconstruction images of RCC during the corticomedullary and nephrogenic phases of enhancement and recommended energy levels for each of the phases. Shi et al (29) found that the proportion of focal enhanced lesions of early gastric cancer in the portal phase displayed in VMI+ reconstructions was 16.1% higher than that in mixed 120 kV polyenergetic images (PEIs). Moreover, in VMI+ reconstructions, the superficial-and excavatedtype lesions, which were not visible in the PEIs, could be found, and consequently, observers can stage early gastric cancer more correctly.…”
Section: Tumormentioning
confidence: 99%
“…These different images, such as monoenergetic images at different energies, iodine maps, and virtual non-contrast images, generate large amounts of data which can be processed. Interestingly, DEsCT has been reported to have great potential in the detection of early gastric cancer and may improve the accuracy of TN staging in gastric cancer patients (11,12).…”
Section: Introductionmentioning
confidence: 99%